2020
DOI: 10.26675/jabe.v5i1.14367
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Excel-Based Exams to Prevent Students from Cheating

Abstract: The COVID19 pandemic has brought a disruption on education, especially on how courses are delivered in higher education. Higher education providers are forced to go online, irrespective of the IT infrastructure’s availability and the capability of lecturers in delivering online courses. While online learning is perceived as an opportunity for academic integrity breaches, academicians need to ensure that processes are in place to avoid students cheating, especially during the exam. This paper presents an innova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In previous studies [10,11], it is shown that students taking online exams have shown lower test anxiety compared to the group with in-class exams. This is possibly due to the high flexibility in online exams, where students can face the test when they feel more prepared, and in a familiar environment with less anxiety-provoking stimuli.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In previous studies [10,11], it is shown that students taking online exams have shown lower test anxiety compared to the group with in-class exams. This is possibly due to the high flexibility in online exams, where students can face the test when they feel more prepared, and in a familiar environment with less anxiety-provoking stimuli.…”
Section: Introductionmentioning
confidence: 91%
“…In order to prevent students from collaborating, the exam can be set to have a limited login time, present questions as they answer without back-tracking, randomize exam questions/answers for different students, and change exam questions every term [42]. A study by Suryani shows that individualized questions can be successfully prepared and scored using the Excel spreadsheet for accounting students based on their student ID numbers [11].…”
Section: Exam Designmentioning
confidence: 99%
“…Despite the fact that students often believe that cheating is not acceptable behavior, many report participating in cheating (Anderman, Griesinger, & Westerfield, 1998). Male students find that there are more opportunities to cheat during online exams than female students (Suryani, 2020). Research shows that male students participate in cheating during exams more often than female students (Cizek, 1999;Dawkins, 2004; DeAndrea, Carpenter, Shulman, & Levine, 2009; Hensley, Kirkpatrick, & Burgoon, 2013), which Whitley, Nelson, & Jones (1999) confirm in their meta-analysis by reviewing the literature.…”
Section: Cheating In the Virtual Classroommentioning
confidence: 99%
“…The massive need to use online forms of exams appeared suddenly, so there is little research devoted to this issue. Some appeared at the end of 2020 in response to the new challenges brought by COVID-19, focusing mainly on general ideas on how to prevent cheating (e.g., Harper, Bretag & Rundle, 2020;Suryani, 2020). Few consider trust, dialog, and awareness as potential improvement tools (e.g., Bucciol, Cicognani & Montinari, 2020).…”
Section: Online Exams During Isolationmentioning
confidence: 99%